Evaluation of the effect of bone plate modulus on the early bone healing of fractured tibia. (15th March 2022) - Zaheer, Muhammad Usama; Mehboob, Hassan; Mehboob, Ali; Chang, Seung-Hwan
Abstract: Metallic implants with high Young's moduli are used to treat long-bone fractures; however, they cause stress shielding and prevent bones from attaining their original strength. Thus, flexible composite implants have been designed to enhance tissue development without stress shielding. Herein, 3D-printed composite bone plates with different Young's moduli were designed, and their effects on 3D models of long-bone fractures were analysed. A biphasic mechano-regulation algorithm, coupled with cell diffusion and tissue phenotype activities, was developed using a Python script to analyse bone-healing patterns for 112 days after surgery. A composite bone plate (Young's modulus, 40 GPa) showed the best healing performance (100%), compared with a stainless-steel bone plate (70%). Further, cell and tissue development using bone plates with different Young's moduli under different loading conditions are presented. Graphical abstract: Image 1